2000
DOI: 10.1366/0003702001949690
|View full text |Cite
|
Sign up to set email alerts
|

Novel SERS-Active Optical Fibers Prepared by the Immobilization of Silver Colloidal Particles

Abstract: A novel sensor based upon surface-enhanced Raman scattering (SERS) has been constructed by immobilizing colloidal silver particles onto the distal end of an optical fiber. This same single fiber was then used to both transport the exciting laser radiation and collect the Raman scattering from analytes sorbed onto the colloidal particles. The colloidal particles were immobilized by functionalization of the end of the optical fiber with (3-aminopropyl)trimethoxysilane prior to immersion of the fiber in silver co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…For the common "optrod" configuration [43], which the fiber is used to both transport the exciting laser radiation and collect the Raman scattering from the analyte, the Raman background of the POF would overwhelm the spectrum of the R6G dye. In this experiment, the light is focused on the tip directly with an inverted microscope objective, which is also used for collecting the signal.…”
Section: Optical Fiber Sers Sensorsmentioning
confidence: 99%
“…For the common "optrod" configuration [43], which the fiber is used to both transport the exciting laser radiation and collect the Raman scattering from the analyte, the Raman background of the POF would overwhelm the spectrum of the R6G dye. In this experiment, the light is focused on the tip directly with an inverted microscope objective, which is also used for collecting the signal.…”
Section: Optical Fiber Sers Sensorsmentioning
confidence: 99%
“…These were stripped of their jackets and then cleaved to produce flat endfaces at both the proximal and distal ends of the fibre. Since these fibres are used in the optrode configuration, wherein they carry both the excitation source and Raman scattered light, the cleaved lengths were kept short, as is common practice in the literature (Polwart et al, 2000;Hill, 1998, 2000a,b), in order to minimize the background Raman contribution from the fibre itself (Ma and Li, 1996).…”
Section: Optical Fibresmentioning
confidence: 99%
“…To date, there have been several attempts in this direction (Viets and Hill, 1998). Simple metal coating of mechanically roughened tips (Mullen and Carron, 1991), metal island formation by slow evaporation (MacDonald et al, 1994), colloidal mask coatings (Stokes and Vo-Dinh, 2000) and the immobilization of metal colloidal particles (Polwart et al, 2000;Shi et al, 2008) have all shown potential. However these techniques rely on fundamentally random formations and as such, have intrinsically limited reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized Au nanoparticles were expected to act as an SERS substrate. 52 When the nanoparticles were exposed to the Rh6G solution, the SERS spectrum clearly showed the Rh6G signature peaks with a small shift from those in solution Figure 9A. Change of spectral positions of the peaks by ±(7-10)cm −1 corresponds to 1.24 meV or 0.12 kJ/mol and is expected for adsorbed molecules.…”
Section: Sersmentioning
confidence: 92%